La persistance du western : Yellowstone, la Nouvelle télévision et l’histoire américaine - Martin Shuster (Cahiers d’histoire.)
This essay will explore the ways in which the western has found new life in new television, especially in the recent neo-western Yellowstone. The paper pursues the significance of the western for both the medium of new television and for the construction of American identity and history. I argue ultimately that while the western has been central to the construction of American identity from its earliest days, recent developments in American identity suggest new qualitative developments for the western as it melds with new television.